(Dis)locating the norms: marginalized subjects as protagonists in here comes the sun - Harris (UERJ), Leila; Affonso (UERJ), Natália (ANTARES: Letras e Humanidades, 2019)
The objective of this article is to reflect on the notions of space and place and, in parallel, on displacement, focusing specifically on the Caribbean space, as outlined by Edouard Glissant (1989) and later Carole Boyce Davies (1994, 2018), among others. The present work is based on decolonial studies that historically situate the origin, constitution and permanence of the modern/colonial power matrix. It is necessary to produce art, knowledge and criticism that move away, subvert, question and reframe colonial, racist and heteropatriarcal normativity, creating spaces for the recuperation, (re)construction and (re)invention of knowledge and ways of being in the world not ruled by Eurocentrism. The focus of the analysis is the debut novel by Jamaican Nicole Dennis-Benn, Here Comes the Sun (2016), which transforms characters marginal to the norms into protagonists.